Hubungan Jarak Tempat Tinggal & Pendapatan Penderita Kanker Payudara Terhadap Kepatuhan Menjalani Kemoterapi di Rumah Sakit Umum Cut Meutia Kabupaten Aceh Utara - Febry Caesariyanto Safar; Adi Rizka; Khairunnisa (PT FORMOSA CENDEKIA GLOBAL, 2022)
Breast cancer is one of the second types of cancer after lung cancer. The purpose of this study was to determine the relationship between place and income of breast cancer patients with adherence to chemotherapy at the Cut Meutia General Hospital, North Aceh Regency. In this study was breast cancer patients who underwent chemotheraphy from March to April 2022 with a total of 115 respondents. The results showed that the main category of respondents had a distance of 112 respondents (97.4%) and income from the main category of 91 respondents (79.1%). The results of the study bivariate analysis test, there was no relationship between residence distance and adherence to chemotheraphy with P value (1,000) and there was no relationship between income and adherence to chemotheraphy with P value (0,752).